Proceedings of the 26th ACM SIGSOFT International Symposium on Software Testing and Analysis 2017
DOI: 10.1145/3092703.3092727
|View full text |Cite
|
Sign up to set email alerts
|

Generating unit tests with descriptive names or: would you name your children thing1 and thing2?

Abstract: The name of a unit test helps developers to understand the purpose and scenario of the test, and test names support developers when navigating amongst sets of unit tests. When unit tests are generated automatically, however, they tend to be given non-descriptive names such as "test0", which provide none of the benets a descriptive name can give a test. The underlying challenge is that automatically generated tests typically do not represent real scenarios and have no clear purpose other than covering code, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 47 publications
0
54
1
Order By: Relevance
“…To further improve maintainability, these assertions can be minimized for their fault-finding potential [21]. Further optimizations for maintainability include applying specific heuristics from industrial application [22], semantic simplification [23], prioritizing using literals taken from the source code [24], generation of meaningful names for tests [25], measuring readability using prediction models [26], and adding textual summaries [27].…”
Section: B Test Case Generationmentioning
confidence: 99%
“…To further improve maintainability, these assertions can be minimized for their fault-finding potential [21]. Further optimizations for maintainability include applying specific heuristics from industrial application [22], semantic simplification [23], prioritizing using literals taken from the source code [24], generation of meaningful names for tests [25], measuring readability using prediction models [26], and adding textual summaries [27].…”
Section: B Test Case Generationmentioning
confidence: 99%
“…The understandability criterion is important because test cases that are generated automatically have a very long format and are difficult to read [6]. Several studies have proposed improving the understanding of test cases by generating documentation in the form of natural language that contains summaries of test cases [41], simplifying test cases from the size of the LOC [40], and giving the name of the identifier that describes contents of test cases [42]. Understandability measurement is often associated with readability criteria because it is assumed that code is easy to read will be easy to understand.…”
Section: Test Case Understandabilitymentioning
confidence: 99%
“…To improve automated test case presentation, Daka optimized the search-based generation test case by using readability evaluation as a secondary fitness function []. Daka has also evaluated whether the readability optimized test case can be better understood by the developer or not [6], [42]. Evaluation of the model was conducted by giving some questions related to the understanding of test cases to 30 students.…”
Section: Test Case Understandabilitymentioning
confidence: 99%
“…Test Understandability Factors. Although human oracle costs can be ameliorated by creating automated test data generation methods that consider readability (e.g., [13], [22]), to the best of our knowledge there is no prior work aiming to characterize and limit the qualitative human oracle costs associated with the automated testing of a database schema. As a first step, we must determine how generated test data affects a human's understanding of a test's behavior.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Grano et al reported that manually written tests are more readable than automated tests [40]. Different approaches have been created to address this issue: test visualization [41], [42], automatic test documentation [38], [43], [44], and test readability improvement [14], [15], [22].…”
Section: Frequency Of Nullmentioning
confidence: 99%